2013
DOI: 10.4137/bic.s10759
|View full text |Cite
|
Sign up to set email alerts
|

1-Hydroxypyrene Levels in Blood Samples of Rats after Exposure to Generator Fumes

Abstract: Polynuclear Aromatic Hydrocarbons (PAHs) are a major component of fuel generator fumes. Carcinogenicity of these compounds has long been established. In this study, 37 Swiss albino rats were exposed to generator fumes at varied distances for 8 hours per day for a period of 42 days and the level of 1-hydroxypyrene in their blood was evaluated. This study also tried to correlate the level of blood 1-hyroxypyrene with the distance from the source of pollution. Plasma was collected by centrifuging the whole blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“… 26 , 27 , 28 Furthermore, blood concentrations of the pyrene metabolite 1‐hydroxypyrene was reported at 26–34 μg/ml in rats exposed to gasoline exhaust. 64 Even the highest concentration used in the present study (50 μg/ml MeOH = 7.5 μg/ml pyrene) is well below blood concentration that can be achieved by in vivo inhalation exposure.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“… 26 , 27 , 28 Furthermore, blood concentrations of the pyrene metabolite 1‐hydroxypyrene was reported at 26–34 μg/ml in rats exposed to gasoline exhaust. 64 Even the highest concentration used in the present study (50 μg/ml MeOH = 7.5 μg/ml pyrene) is well below blood concentration that can be achieved by in vivo inhalation exposure.…”
Section: Discussionmentioning
confidence: 57%
“…[26][27][28] Furthermore, blood concentrations of the pyrene metabolite 1-hydroxypyrene was reported at 26-34 μg/ml in rats exposed to gasoline exhaust. 64 Even the highest concentration used in the present study (50 μg/ml Organic chemicals extracted from diesel exhaust may affect expression and secretion of pro-inflammatory mediators, as well as expression of β-adrenergic receptors and aryl hydrocarbon receptor-regulated genes in primary human adipocytes. These chemicals thus carry potential to disturb expression of genes linked to disease in adipose tissue.…”
Section: Discussionmentioning
confidence: 73%
“…This is in agreement with Ifegwu et al who in their study of the effects of generator fumes on blood levels of 1-hydroxypyrene in rats concluded that the ability of PAHs to form adducts with DNA is an indication of their carcinogenicity, by checking the levels of 1-hydroxypyrene in blood-a metabolic product of pyrene -which is a prominent marker for PAH exposure. 9 The genotoxicity of some components of generator fumes implies that the adverse effects of inhalation can be passed on to generations yet unborn. Previous…”
Section: Discussionmentioning
confidence: 99%
“…8 A study showed that generator fumes contained levels of poly-aromatic hydrocarbons (PAHs) capable of increasing the risk of cancer in an environment where generator use is common. 9 Other reported adverse effects of exhaust pollutants included increased infant mortality, acute heart attacks, chronic deficits in lung development of children aged 10-18 years, and ovarian cancer. [10][11][12][13] Numerous epidemiological studies have also shown that exposure to a large amount of petroleum-related particles causes an increase in morbidity and mortality, which often arises from respiratory diseases and their negative impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The immunoinflammatory and oxidative stress responses associated with stressors depend mainly on the degree of exposure. 1,[8][9][10] Toxic fumes from anthropogenic activities, including petroleum product fumes (PPFs), vehicular exhaust, [11][12][13][14] present in ambient air pester the tracheal and lungs byways of inhaled polluted air, occupationally or as a result of careless regular daily activities. 15 Environmentally, PPF is ubiquitous, and a common source of contact is from petrol (gasoline) dispensing station (PDS), 13,16,17 marketing various petroleum products, especially-petrol (gasoline), kerosene, and diesel.…”
Section: Introductionmentioning
confidence: 99%